Attentional selection of multiple objects in the human visual system - Zhang, Xilin (Neuroimage, 2017)
Classic theories of object-based attention assume a single object of selection but real-world tasks, such as driving a car, often require attending to multiple objects simultaneously. However, whether object-based attention can operate on more than one object at a time remains unexplored. Here, we used functional magnetic resonance imaging (fMRI) to address this question as human participants performed object-based attention tasks that required simultaneous attention to two objects differing in either their features or locations. Simultaneous attention to two objects differing in features (face and house) did not show significantly different responses in the fusiform face area (FFA) or parahippocampal place area (PPA), respectively, compared to attending a single object (face or house), but did enhance the response in the inferior frontal gyrus (IFG). Simultaneous attention to two circular arcs differing in locations did not show significantly different responses in the primary visual cortex (V1) compared to attending a single circular arc, but did enhance the response in the intraparietal sulcus (IPS). These results suggest that object-based attention can simultaneously select at least two objects differing in their features or locations, processes mediated by the frontal and parietal cortex, respectively.